Does Sharing Memories Make Us Feel Closer? The Roles of Memory Type and Culture - Guan, Li; Wang, Qi (Journal of cross-cultural psychology, 2022)
The present research examined the effects of sharing different types of memories on perceived relationship closeness and how that is related to psychological well-being in a cross-cultural context. In two studies, European American and Asian participants (total N = 714) reported their feelings of closeness to a conversation partner in hypothetical situations that involved five types of information sharing: specific and general autobiographical memories, specific and general vicarious memories, and non-person information. Sharing memories led to greater feelings of closeness than sharing non-person information in both groups. Asians felt closer to the conversation partner than European Americans across all types of information sharing. Sharing autobiographical and specific memories led to greater closeness than sharing vicarious and general memories in both groups, although sharing specific autobiographical memories appeared most effective for relationship closeness for European Americans. Perceived relationship closeness following conversational exchanges was positively associated with psychological well-being across cultures.